The origin of the family, private property, and the state - Engels, Friedrich (London Anodos Books, 2019)
Friedrich Engels explores the interrelated development of the family and the state from the ancient world to the Victorian era. Drawing on the anthropological theories of his time, Engels argues that class-based societies overthrew their matriarchal predecessors, replacing a communal, polygamous culture with one that was monogamous and property-bound"-- Provided by publisher.
Includes bibliographical references and index
Keywords: Primitive societies-Families--History